2015
DOI: 10.1002/hec.3158
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Healthcare Providers' Performances Within Managed Competition Using Multidimensional Quality and Cost Indicators

Abstract: There is substantial heterogeneity between diabetes care groups' performances as measured using multidimensional indicators on quality and costs. Better quality diabetes care can be achieved with lower or higher costs. Routine monitoring using multidimensional data on quality and costs merged at the individual level would allow a systematic and comprehensive analysis of healthcare providers' performances within managed competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
(38 reference statements)
5
8
0
Order By: Relevance
“…This interpretation is consistent with recent work conducted by Cutler, Skinner, Stern, and Wennberg () and Finkelstein et al () who found that patient demand is not as important in explaining regional variations in health care expenditures and that the organization of care and providers' behavior play a major role. Such an interpretation concurs with studies, such as that performed by Portrait, van der Galiën, and Van den Berg (), who showed that in the Netherlands, substantial heterogeneity exists between diabetes care groups' performances as measured using multidimensional indicators of quality and costs. Brekke, Holmås, Monstad, and Straume () attempted to understand the source of this variation.…”
Section: Discussionsupporting
confidence: 90%
“…This interpretation is consistent with recent work conducted by Cutler, Skinner, Stern, and Wennberg () and Finkelstein et al () who found that patient demand is not as important in explaining regional variations in health care expenditures and that the organization of care and providers' behavior play a major role. Such an interpretation concurs with studies, such as that performed by Portrait, van der Galiën, and Van den Berg (), who showed that in the Netherlands, substantial heterogeneity exists between diabetes care groups' performances as measured using multidimensional indicators of quality and costs. Brekke, Holmås, Monstad, and Straume () attempted to understand the source of this variation.…”
Section: Discussionsupporting
confidence: 90%
“…Hospital quality, Q i , is the final variable in the cost equations. Prior research by Portrait et al () supports a positive expectation regarding the sign of this variable. Lastly, C i ( CQ i ) is expected to retain a positively signed coefficient estimate in the pricing equations, as hospitals of all types are expected to engage in some degree of markup.…”
Section: Data and Econometric Modelsmentioning
confidence: 73%
“…Using the Dutch experience with managed competition, Portrait, Galiën, and van den Berg () develop a strategy to assess the relative performance of health care providers using data on quality and costs . Using a sample of 2,409 clients from about 20 diabetes care groups, these researchers conduct “a cost‐consequences analysis” suggesting that the link between quality of care and costs is ambiguous, as improvement in the quality of diabetes care is found to accompany either lower or higher costs (Portrait et al, ). This study is particularly relevant to the current research, given that we examine the impact of hospital quality on the costs of various medical procedures.…”
Section: Prior Literature: a Brief Reviewmentioning
confidence: 99%
“…We used 2008 and 2012 Diagnosis-based Cost Groups (DCGs), which are cost-profiles of the diseases based on diagnosis information [ 21 ] and PCGs from the Dutch risk equalization model [ 19 ], each referring to data from previous years. Using claims data from previous years may tackle the endogeneity issues that arise when using spending and health data from the same year [ 22 ]. The DCG variable ranged from 0 to 13 or 15 (13 clusters for 2008 and 15 for 2012) where a higher DCG number is equal to being in a higher cost cluster.…”
Section: Methodsmentioning
confidence: 99%